Cloning cDNA sequence coding the KSA-1 lectin from red alga Kappaphycus striatum cultivated in Vietnam - Hung, Le Dinh; Trung, Dinh Thanh (Vietnam Journal of Biotechnology, 2018)
The red alga Kappaphycus striatum is economically important food species and extensively cultivated in Vietnam. This cultivated alga may thus now contribute as a source of not only carrageenan, but also other bioactive compounds for biochemical and medicinal uses. KSA-1 lectin from this alga has been evaluated for biochemical properties, including high-mannose binding specificity, N-terminal amino acid sequence and molecular mass. In this study, we have cloned the cDNA clone encoding the lectin KSA-1. The full-length sequence of cDNA clone of KSA-1 lectin encoded a polypeptide of 268 amino acids including initiating methionine, with four tandemly repeated domains of about 67 amino acids, and sharing 43% sequence identity. The primary structure and the amino acid residues interact with mannopentaose core structure per a repeat domain of the KSA-1 lectin highly resemble and match those of anti-virus the lectin family in lower organinsms, including bacteria [BOA from Burkholderia oklahomensis EO147, MBHA from Myxococcus xanthus and PFA from Pseudomonas fluorescens Pf0-1], cyanobacteria [OAA from Oscillatoria agardhii] and red algae [ESA-2 from Eucheuma serra, EDA-2 from Eucheuma denticulatum, KAA-1 and KAA-2 from Kappaphycus alvarezii and KSA-2 from K. striatum]. Analysis of predicted secondary structure of KSA-1 showed twenty β-strands. Each repeated domain comprises the five β-strands and matches with number of β-strands of BOA lectin. Therefore, the red alga K. striatum could be a good source for application in biomedicine and biochemistry as materials for production of the functional lectin(s).